PENERAPAN MODEL JIGSAW MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V - Muhammad Rizal Fauzi; Lovika Ardana Riswari; Diana Ermawati (STKIP Subang, 2023)
Learning is said to be effective if students get maximum results. Mathematics learning outcomes at state elemanatry school 1 Gemiring Kidul are relatively low. This is influenced because students do not really understand the learning material, because learning in class seems boring and only uses the lecture method. The purpose of this study is to improve mathematics learning outcomes through the application of the Jigsaw model with the aid of the barung media (Bangun Ruang). Learning outcomes are the level of success of the learning process carried out by students with teacher guidance which is characterized by increased knowledge and skills as well as attitude development. The Jigsaw learning model focuses on group work in the form of small groups. Group members are responsible for the success of the group and the completeness of the material being studied can be informed to other groups. Barung media is a concrete or real medium for building cubes and blocks. This research is a classroom action research conducted for 2 cycles, each student consists of 2 meetings. And consists of 4 stages, namely: planning, implementing actions, observing, and reflecting. The subjects of this study were teachers and fifth grade students of state elemanatry school 1 Gemiring Kidul, totaling 29 students, consisting of 16 boys and 13 girls. Data collection techniques by observation, interviews, and documentation. With quantitative and qualitative data analysis techniques.